(untitled) (Journal of Organizational Psychology, 2020)
This study focuses on positive dispositional traits and mentoring in the study of strategic independence among young adults. Strategic independence is a composite trait comprised used to assess a person’s propensity to make and persevere with long-term plans. Using hierarchical regression analysis on survey data collected from 324 young adults in the United States, we found that effective mentoring relationships have a positive influence on the level of strategic independence among mentees. Implications for theory and practice, limitations, and future research are discussed.